Evaluating maternal health service coverage across districts of Himachal Pradesh, India through composite index approach - Chauhan, Anjali; Sharma, Komal; Sethi, Gaurav (International Journal Of Community Medicine And Public Health, 2024)
Despite advancements in maternal health in India, disparities in service coverage persist, particularly in rural and challenging regions. This study evaluates the maternal health service coverage index (MHSI) in Himachal Pradesh, a predominantly hilly state with a largely rural population. By calculating this composite index, the study aims to identify disparities in service utilization across districts. The findings will inform targeted interventions to improve maternal health outcomes and address inequalities within the state. A retrospective analysis was conducted using maternal health indicators from the health management information system (HMIS) report of Himachal Pradesh from March 2020 to April 2024. Separate indices for antenatal, perinatal, and postnatal services were calculated which were then combined into a composite index (MHSI) using arithmetic mean method. The analysis revealed significant disparities in maternal health service coverage across districts. Districts like Bilaspur, Mandi, and Shimla consistently showed high composite indices, indicating robust maternal health services. In contrast, remote districts such as Lahul and Spiti, Kinnaur, and Chamba faced challenges in service coverage, particularly in antenatal care (ANC) and perinatal care. The findings highlight significant disparities in maternal health service coverage across Himachal Pradesh, particularly in remote districts (Lahaul-Spiti and Kinnaur). These disparities underscore the need for targeted interventions to improve access to and utilization of maternal health services in underserved regions.